2000
DOI: 10.1007/bf03019479
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of cerebral hyperemia with anti-hypertensive medication after electroconvulsive therapy

Abstract: REPORTS OF INVESTIGATION 767CAN J ANESTH 2000 / 47: 8 / pp [767][768][769][770][771][772][773][774] Purpose: Several different anti-hypertensive regimens have been introduced for the prevention of systemic hyperdynamic responses after electrically induced seizures. In the present study, the effects of anti-hypertensive medications on cerebral circulation were studied.Methods: Systemic blood pressure was controlled by several anti-hypertensive medications, nicardipine, prostaglandin E1, alprenolol and nitroglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…Recently, Fabbri et al [57] demonstrated that this phenomenon is not only observed in bilateral ECT but also in unilateral ECT. Because cerebrovascular hemodynamic alteration during ECT is partly provoked by systemic hemodynamic changes, antihypertensive regimens that prevent systemic hypertension during ECT ameliorate cerebrovascular hemodynamic alteration to some extent [58]. However, antihypertensive medication that can prevent systemic hypertension cannot completely suppress the reactive acceleration in middle cerebral artery blood flow.…”
Section: Cerebral Circulationmentioning
confidence: 97%
“…Recently, Fabbri et al [57] demonstrated that this phenomenon is not only observed in bilateral ECT but also in unilateral ECT. Because cerebrovascular hemodynamic alteration during ECT is partly provoked by systemic hemodynamic changes, antihypertensive regimens that prevent systemic hypertension during ECT ameliorate cerebrovascular hemodynamic alteration to some extent [58]. However, antihypertensive medication that can prevent systemic hypertension cannot completely suppress the reactive acceleration in middle cerebral artery blood flow.…”
Section: Cerebral Circulationmentioning
confidence: 97%
“…Measurements were initiated prior to ECT and were terminated at the end of the procedure. Anesthesia was induced using thiopentone (2 mg/kg intravenously over 15 s) [6] followed by succinylcholine (1 mg/kg intravenously). Assisted mask ventilation was initiated with 100% oxygen.…”
Section: Case Reportmentioning
confidence: 99%
“…In order to prevent ECT-induced changes in systemic hemodynamics, investigators have used various antihypertensive agents [1,2], including alprenolol, nitroglycerin, nicardipine, esmolol, and labetalol [1]. We previously demonstrated that beta-blockers could effectively prevent an increase in heart rate when compared with other drugs [6,7].…”
Section: Introductionmentioning
confidence: 98%
“…4,5 In one study, alprenolol partially attenuated cerebral blood flow elevation at a dose which prevents blood pressure (BP) elevation. 6 Although esmolol is often used during ECT, there has been no report describing the effect of the ultra-short acting ß-adrenergic-blocking drugs on cerebral blood flow during ECT.…”
Section: Lectroconvulsive Therapy (Ect)mentioning
confidence: 99%
“…The difference in the number of patients in the two studies is derived from the difference in standard deviation of mean BP and cerebral blood flow velocity in our previous studies. 6,9 These patients were suffering from endogenous depression, and were in good physical health. No patient had cardiovascular or cerebrovascular complications, such as ischemic heart disease, hypertension, arrhythmia, cerebral infarction, intracranial aneurysm, arteriovenous malformation, or drug allergies.…”
Section: Patientsmentioning
confidence: 99%